An industrial quality control study on Caltex Philippines, Inc. - Manuel, Maria Theresa (College of Engineering, 2006)
Caltex Philippines, Inc. is among the largest and leading oil manufacturing company here in the Philippines. It provides different petroleum products that are known for their quality. Being one of the leading oil companies, a good quality system is crucial for Caltex o maintain its current market share. Although the company practices Statistical Process Control (SPC), interpretation of data is not performed. Thus, any shift in the process or any out of control point is not immediately dealt with. For this reason, the proponents performed this industrial quality control study on Caltex which would help ensure not only the management of Caltex but more importantly the consumers, that the products undergo appropriate quality measures. The study focused on the Supply Chain Philippines--the quality assurance and laboratory services of Caltex. In this study, the group focused on the quality characteristics of a certain lubricant, which in this study is referred to as Lubricant X. The test methods analyzed are the tests for viscosity, mass% calcium content and mass% zinc content. The said quality characteristics are measured after the blending of raw materials, namely, base oil and additives, in order to produce the lubricant. After performing SPC on these quality characteristics, it was found out that calcium content is in statistical control but the process is off-centered and is not capable with Cpk < Cp (0.95<0.99). For the zinc content, the process is out of control, off centered but it is capable with Cpk < Cp (0.54 < 1.07). Lastly, the viscosity is out of control, off centered but capable with Cpk < Cp (0.97<0.98). The main causes of the problems were found to be related to the formulation of oil components, blending and testing operations. The control measures recommended by the researchers include training, strict implementation of SPC and continuous process monitoring to enhance the future operations of Caltex. These will lessen the deviations from specifications of the lubricant, and maintain and improve its quality. An implementation plan was also provided as a guide for the company.